Complex Systems Design & Management Asia : Smart Nations - Sustaining and Designing: Proceedings of the Second Asia-Pacific Conference on Complex Systems Design & Management, CSD&M Asia 2016 - Cardin, Michel-Alexandre.; Chuen, Lui Pao.; Fong, Saik Hay.; Krob, Daniel; Tan, Yang How. (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book contains all refereed papers that were accepted to the second edition of the Asia-Pacific conference on " Complex Systems Design and Management Asia" (CSD&M Asia 2016) that took place in Singapore from February 24 to February 26, 2016 (Website: http://www.2016.csdm-asia.net/). These proceedings cover the most recent trends in the emerging field of Complex Systems, both from an academic and a professional perspective. A special focus is put on Smart Nations: Designing and Sustaining. The CSD&M Asia 2016 conference is organized under the guidance of the Singapore division of the Center of Excellence on Systems Architecture, Management, Economy and Strategy (CESAMES) - Legal address: C.E.S.A.M.E.S. Singapore - 16 Raffles Quay - #38-03 Hong Leong Building - Singapore 048581 (website : http://www.cesames.net/en - email: contact@cesames.net).
The Need for Technology Policy Programs: Example of Big Data -- The Need for Technology Policy Programs: Example of Big Data -- Framework for Managing System-of-Systems Ilities -- Expansionism-Based Design and System of Systems -- A General Framework for Critical Infrastructure Interdependencies Modeling Using Economic Input-output Model and Network Analysis -- Introducing Cyber Security at the Design Stage of Public Infrastructures: A Procedure and Case Study -- Ontology for Weather Observation System -- Renewable Integration in Island Systems { a System Dynamics Assessment -- A Systematic Approach to Safe Coordination of Dynamic Participants in Real-time Distributed Systems -- Foresight Study on Singapore Urban Mobility: Methodologies and Preliminary Insights -- Managing the Embedded Systems Development Process with Product LifeCycle Management -- Establishment of Model-Based Systems Engineering Approach for Rapid Transit System Operation Analysis -- A Model-Based Testing Process for Enhancing Structural Coverage in Functional Testing -- Design for Aordability from System to Programme to Portfolio Using Tradespace-based Aordability Analysis: An Application to a Federated Satellite System Design Case Study -- An Optimization Framework for Terminal Sequencing and Scheduling: The Single Runway Case -- Holistic Integrated Decisions Trade-O Analysis-Baseline for an Optimal Virtual IP Multimedia Subsystem (IMS) -- Portfolio Decision Technology for Designing Optimal Syndemic Management Strategies -- Using Social Sciences to Enhance the Realism of Simulation for Complex Urban Environments -- Inferring Activities and Optimal Trips: Lessons from Singapore's National Science Experiment -- Modelling Resilience in Interdependent Infrastructures: Real-world Considerations -- 3DExperience Platform, System Engineering Workbench for Multi-View Systems Methodology. The Aircraft RADAR Use Case -- The Methodology to Integrate the Information Concerned About the Safety Between Many Kinds of Materials About the Space System -- Information Architecture for Complex Systems Design and Management -- A CLEAN way for Sustainable Solid Waste Management System forSingapore -- Mexico Ciudad Segura -- Product Line Management - onvergence Architecture, Market and Operational Gains.
Description based on publisher-supplied MARC data.
Keywords: Artificial intelligence; Computational intelligence; Urban geography; Computational Intelligence; Artificial Intelligence; Urban Geography / Urbanism (inc. megacities, cities, towns).